Understanding the medication safety challenges for patients with mental illness in primary care: a scoping review - Matthew J. Ayre; Penny J. Lewis; Richard N. Keers (BMC Psychiatry, 2023)
Abstract Background Mental illness and medication safety are key priorities for healthcare systems around the world. Despite most patients with mental illness being treated exclusively in primary care, our understanding of medication safety challenges in this setting is fragmented. Method Six electronic databases were searched between January 2000-January 2023. Google Scholar and reference lists of relevant/included studies were also screened for studies. Included studies reported data on epidemiology, aetiology, or interventions related to medication safety for patients with mental illness in primary care. Medication safety challenges were defined using the drug-related problems (DRPs) categorisation. Results Seventy-nine studies were included with 77 (97.5%) reporting on epidemiology, 25 (31.6%) on aetiology, and 18 (22.8%) evaluated an intervention. Studies most commonly (33/79, 41.8%) originated from the United States of America (USA) with the most investigated DRP being non-adherence (62/79, 78.5%). General practice was the most common study setting (31/79, 39.2%) and patients with depression were a common focus (48/79, 60.8%). Aetiological data was presented as either causal (15/25, 60.0%) or as risk factors (10/25, 40.0%). Prescriber-related risk factors/causes were reported in 8/25 (32.0%) studies and patient-related risk factors/causes in 23/25 (92.0%) studies. Interventions to improve adherence rates (11/18, 61.1%) were the most evaluated. Specialist pharmacists provided the majority of interventions (10/18, 55.6%) with eight of these studies involving a medication review/monitoring service. All 18 interventions reported positive improvements on some medication safety outcomes but 6/18 reported little difference between groups for certain medication safety measures. Conclusion Patients with mental illness are at risk of a variety of DRPs in primary care. However, to date, available research exploring DRPs has focused attention on non-adherence and potential prescribing safety issues in older patients with dementia. Our findings highlight the need for further research on the causes of preventable medication incidents and targeted interventions to improve medication safety for patients with mental illness in primary care.